Efficacy and safety of early parenteral anticoagulation as a bridge to warfarin after mechanical valve replacement - Mathew, Joseph G.; Spyropoulos, Alex C.; Yusuf, Arif; Vincent, Jessica; Eikelboom, John; Shestakovska, Olga; Fremes, Stephen; Noora, Joseph; Guo, Linrui; Peterson, Mark; Pai, Menaka; Whitlock, Richard (Thrombosis and Haemostasis, 2014)
Limited evidence exists to guide the use of early parenteral anticoagulation following mechanical heart valve replacement (MVR). The purpose of this study was to compare the 30-day rates of thrombotic and bleeding complications for MVR patients receiving therapeutic versus prophylactic dose bridging regimens. In this retrospective cohort study we reviewed anticoagulation management and outcomes of all patients undergoing MVR at five Canadian hospitals between 2003 and 2010. The primary efficacy outcome was thromboembolism (stroke, transient ischaemic attack, systemic embolism or valve thrombosis) and the primary safety outcome was major bleeding at 30-days. Outcomes were compared using a logistic regression model adjusting for propensity score and in a 1:1 propensity matched sample. A total of 1777 patients underwent mechanical valve replacement, of whom 923 received therapeutic dose bridging anticoagulation and 764 received prophylactic dose bridging postoperatively. Sixteen patients (1.8 %) who received therapeutic dose bridging and fifteen patients (2.1 %) who received prophylactic dose bridging experienced the primary efficacy outcome (odds ratio [OR] 0.90; 95 % confidence interval [CI], 0.37 to 2.18, p=0.81). Forty-eight patients (5.4 %) in the therapeutic dosing group and 14 patients (1.9 %) in the prophylactic dosing group experienced the primary safety outcome of major bleeding (OR 3.23; 95 % CI, 1.58 to 6.62; p=0.001). The direction of the effects, their magnitude and significance were maintained in the propensity matched analysis. In conclusion, we found that early after mechanical valve replacement, therapeutic dose bridging was associated with a similar risk of thromboembolic complications, but a 2.5 to 3-fold increased risk of major bleeding compared with prophylactic dose bridging.
Keywords: Cardiac surgery; valvular heart diseases; anticoagulants; heparin; thromboembolism